2014
DOI: 10.3791/51257
|View full text |Cite
|
Sign up to set email alerts
|

Towards Biomimicking Wood: Fabricated Free-standing Films of Nanocellulose, Lignin, and a Synthetic Polycation

Abstract: Woody materials are comprised of plant cell walls that contain a layered secondary cell wall composed of structural polymers of polysaccharides and lignin. Layer-by-layer (LbL) assembly process which relies on the assembly of oppositely charged molecules from aqueous solutions was used to build a freestanding composite film of isolated wood polymers of lignin and oxidized nanofibril cellulose (NFC). To facilitate the assembly of these negatively charged polymers, a positively charged polyelectrolyte, poly(dial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Since buffer rinsing was used between CML and PDADMAC adsorption experiment, the existence of complexes postulates the detachment of PDADMAC from the adsorbed layer for complexation with CML in the solution, supporting the illustration of Figure . Comparably, a thinner film (23.4 ± 2.8 nm) after 16 layers of adsorption was reported for the deposition of three polymers of PDADMAC, unmodified lignin, and NC (nanocellulose with carboxylic acid content of 1 mmol/g) by Pillai and co-workers . In the current and abovementioned studies, PDADMAC did not change the thickness of LBL significantly.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Since buffer rinsing was used between CML and PDADMAC adsorption experiment, the existence of complexes postulates the detachment of PDADMAC from the adsorbed layer for complexation with CML in the solution, supporting the illustration of Figure . Comparably, a thinner film (23.4 ± 2.8 nm) after 16 layers of adsorption was reported for the deposition of three polymers of PDADMAC, unmodified lignin, and NC (nanocellulose with carboxylic acid content of 1 mmol/g) by Pillai and co-workers . In the current and abovementioned studies, PDADMAC did not change the thickness of LBL significantly.…”
Section: Resultssupporting
confidence: 65%
“…Comparably, a thinner film (23.4 ± 2.8 nm) after 16 layers of adsorption was reported for the deposition of three polymers of PDADMAC, unmodified lignin, and NC (nanocellulose with carboxylic acid content of 1 mmol/g) by Pillai and co-workers. 67 In the current and abovementioned studies, PDADMAC did not change the thickness of LBL significantly. However, it highlighted the importance of the linking layer in which the sequential layer buildup was not possible without it.…”
Section: ■ Results and Discussionmentioning
confidence: 44%
“…Engström et al for instance studied the deposition and adhesion of latex nanoparticles on surfaces of cellulose nanofibrils by QCM-D, and have found that the particle softness, which can be modulated via the glass transition temperature of the polymers, was a key parameter for producing strong and tough materials of high nanocellulose content (Engström et al 2019;Engström et al 2017). Similar QCM studies have been carried out on CNC substrates for food packaging (Saini et al 2016), biomimicking wood (Pillai et al 2014) and enzymatic hydrolysis applications (Lin et al 2019). Finally, studies combining AFM and QCM have been performed using proteins, antibodies or enzymes (Raghuwanshi and Garnier 2019), showing again the importance of nanocellulose substrates in producing model substrates for material science or biochemistry studies.…”
Section: -Introductionmentioning
confidence: 86%
“…In the last decade there had been tremendous developments in nanotechnology science, which resulted in the establishment of several new techniques for research. Nanotechnology has achieved the rate of combing all living organisms-plants, animal and microorganisms [1][2][3][4][5][6][7]. It includes multidisciplinary research interest like Biochemistry, Material Science, Polymer Science and etc.…”
Section: Introductionmentioning
confidence: 99%